Analisis berpikir kritis dalam pemecahan masalah matematika ditinjau dari adversity quotient - Yuristina, Hana; Indiati, Intan; Endahwuri, Dhian (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This study aims to describe students' critical thinking in solving mathematical problems in the material of Two Variable Linear Equation Systems and to find out the factors that influence students' critical thinking processes in terms of students' Adversity Quotient. This type of research is descriptive qualitative research. This research was conducted at SMPN 2 Karangtengah in 2020/2021. The subjects of this study were 5 students of class VIII A, namely 2 students with AQ quitter, 2 students with AQ camper, and 1 student with AQ climber. The instrument in this study was given an AQ questionnaire for subject taking, a written test of solving mathematical problems on the material of Two Variable Linear Equations and interviews. The results showed that two students with the AQ quitter level had the ability to think, namely very less critical on the UK subject only fulfilling the Clarification indicator, Inference and the MIN subject only met the Clarification indicator, 2 students with the AQ camper level had the ability to think critically, namely critical by both subjects namely the INA subject and the LS subject fulfill the critical thinking aspects of clarification, assessment, inference, and strategies but several indicators are not answered and fulfilled correctly by the LS subject are found in the inference indicator and INA is on the assessment indicator, and AQ camper has the ability to think critically, which is very critical because the ESA subject fulfills six indicators of critical thinking, namely clarification, assessment, inference, and strategies. factors that cause students' lack of critical thinking skills, including students who are less trying to deal with existing problems and challenges, students do not understand the material taught by the teacher at school, lack of student interaction in classroom learning, lack of curiosity or think more deeply in solving problems.